The direct and indirect effects of brand trust on attitudinal and behavioral loyalty toward SME brands in Klang Valley restaurant sector - Ong, Chuan Huat (2016)
There is a rising interest in Small and Medium sized enterprises (SME) branding to boost business performance. Despite that, less is known about how branding strategies influence business performance through customer’s loyalty. Hence, this study aims to test a model built based on social exchange theory on the role of brand trust (namely, emotional and rational-based trust) in bridging the gap between internal branding strategies (namely, brand experience and brand personality) on customer’s loyalty (namely, attitudinal loyalty and behavioral loyalty). To achieve the following objectives, 242 customers’ responses were obtained through an intercept survey at 10 restaurant outlets of successful SME brands in Klang Valley. Data were analyzed using PLS. The findings reveal that the brand experience has a significant positive relationship with both components of brand trust and brand loyalties. Brand personality, however, has a significant positive relationship with the component of emotional and rational trust, and behavioral loyalty only. Meanwhile, the component of emotional and rational trust has a significant positive relationship with attitudinal and behavioral loyalties. With regards to the mediation role of brand trust, the rational-based trust mediates the relationship between brand experience and attitudinal and behavioral loyalties. Whereas the emotional-based trust only mediates the relationship between brand experience and behavioral loyalty. No mediating effect is found of the emotional and rational-based trust on the relationship between brand personality and brand loyalty.